KAJIAN PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN DAN HASIL KANGKUNG DARAT (Ipomoea reptans): Kangkung Darat, Pertumbuhan, Pupuk Kandang Kambing. - vianney, sultan; Siswadi, Siswadi; Sumarmi, Sumarmi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2024)
This research, entitled Study of Goat Manure on the Growth and Yield of Land Water Spinach ( Ipomoea reptans ), was carried out in Dukuh Jangganan, Kemiri Village, Kemiri Subdistrict, Kebakkramat District, Karanganyar Regency, from June to July 2024. This research aims to examine the provision Dosage of goat manure on the growth and yield of land kale ( Ipomoea reptans ). The experimental design used was a Completely Randomized Design (CRD) with a single treatment factor which was repeated 4 times and 6 treatments. The doses given were D0 without treatment dose (control), D1 goat manure 100 gr/polybag, D2 goat manure 200 gr/polybag, D3 goat manure 300 gr/polybag, D4 goat manure 400 gr/polybag, D5 manure goat 500 gr/polybag. The observation data was tested using the test of variance (ANOVA) and continued with the Least Significant Difference (LSD) test with a level of 5%. The parameters observed include; plant height, number of leaves, leaf length, leaf width, number of tillers, wet weight, crown weight, dry weight. The results of the research showed that the best dose given the highest shoot weight results was achieved in the D3 treatment with a dose of 300 gr/polybag goat manure.